2019
DOI: 10.1039/c9sc01724k
|View full text |Cite
|
Sign up to set email alerts
|

β-Strand inspired bifacial π-conjugated polymers

Abstract: β-Strand inspired bifacial π-conjugated polymers that are soluble despite the absence of pendant solubilizing chains are reported. Precise tunability of the bifacial monomer height enables control of polymer solubility and intermolecular interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…In poly [8]CPP-random- [10]CPP, the fluorescence of the smaller hoops dominates the overall emission spectrum, indicating energy transfer between the hoop units. A related effect was recently observed in a heterocatenane composed of [9]CPP and [12]CPP. [41] Our observation of energy transfer in CPP copolymers suggests that CPP units can play a role in advanced emissive materials composed of multiple fluorophores.…”
Section: Major Breakthroughs In Polymer Chemistry In Recent Decadessupporting
confidence: 58%
See 2 more Smart Citations
“…In poly [8]CPP-random- [10]CPP, the fluorescence of the smaller hoops dominates the overall emission spectrum, indicating energy transfer between the hoop units. A related effect was recently observed in a heterocatenane composed of [9]CPP and [12]CPP. [41] Our observation of energy transfer in CPP copolymers suggests that CPP units can play a role in advanced emissive materials composed of multiple fluorophores.…”
Section: Major Breakthroughs In Polymer Chemistry In Recent Decadessupporting
confidence: 58%
“…For example, unlike in their linear counterparts, the HOMO-LUMO energy gap of CPPs decreases as the number of linked benzene rings decreases. This trend is also reflected in the red-shifting fluorescence emission as the hoop size decreases- [12]CPP has an emission maximum at 450 nm while [7]CPP emits at 587 nm. [19] Small structural changes, such as incorporation of donoracceptor motifs [20] or shifting the position of a bond, [21] can also be used to tune the electronics and optical properties of these molecules.…”
Section: Major Breakthroughs In Polymer Chemistry In Recent Decadesmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on our previous studies on cyclophane-based polymers, bifacial cyclophanes are shown to hinder p-p-interactions. 34 Even though the cyclophanes in H-mers are located only at the periphery and not on the benzimidazole and the rungs, they are efficient in masking the p-surface of H-mers and hindering p-p interactions in the aggregated state. In addition to this, the twist between the strands and rung in the H-mers also hinders the intermolecular p-p aggregation in thin films and therefore results in no significant changes in the absorption spectra of H-mers in solution and thin films.…”
Section: Resultsmentioning
confidence: 99%
“…The benzimidazole H-mers synthesized so far use conventional pendant solubilizing chains to impart solubility. 24 To obtain soluble H-mers, herein, we have employed bifacial cyclophanes that were reported by our group recently 34 and were shown to impart solubility to polymers without the need for pendant solubilizing chains. All the H-mers are readily soluble without heating in chloroform and dichloromethane.…”
Section: Introductionmentioning
confidence: 99%